DYNAMICS OF ADVERTISING AND INCENTIVES IN INCREASING SALES OF SUPERIOR PRODUCTS: ANALYSIS OF ITS INFLUENCE ON CONSUMER PREFERENCES AND RETAILER STRATEGIES - Yulianty, Farida; Saepudin, Didin; Aripin, Zaenal (Organisasi Kreatif Indonesia Emas, 2024)
Advertising and incentive dynamics play a crucial role in marketing strategies to increase sales of superior products. Effective advertising can strengthen consumer awareness of brands and products, while incentives can provide additional encouragement for consumers to choose certain products. However, it is important to understand how the interaction between advertising dynamics and incentives influences consumer preferences and retailer strategies. This research aims to analyze the influence of advertising dynamics and incentives on consumer preferences and retailer strategies in increasing sales of superior products. The research method used is qualitative using literature analysis and case studies. Data sources used include scientific journals, articles and books that are relevant to the research topic. The research results show that advertising dynamics and incentives have a significant influence on consumer preferences and retailer strategies. Effective advertising can create greater awareness of superior products and influence consumer behavior, while incentives can be a determining factor in consumer purchasing decisions. Good integration of advertising, incentives, and dilution strategies can create a holistic, integrated marketing experience for consumers, which can increase product awareness, preference, and purchases.